The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1074/jbc.274.3.1759
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-specific Transcription of the α1(VI) Collagen Gene

Abstract: Analysis of the chromatin of different cell types has identified four DNase I-hypersensitive sites in the 5-flanking region of the ␣1(VI) collagen gene, mapping at ؊4.6, ؊4.4, ؊2.5, and ؊0.1 kilobase (kb) from the RNA start site. The site at ؊2.5 kb was independent from, whereas the other three sites could be related to, ␣1(VI) mRNA expression. The site at ؊0.1 kb was present in cells expressing (NIH3T3 and C2C12) but absent in cells not expressing (EL4) the mRNA; the remaining two sites were apparently relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…6, b and c). As previously observed, one, indicated by * in the figure, was an invariant site present in all cells, whereas a second site, HS1, mapping at about Ϫ0.1 kb, was detectable in all cells expressing ␣1(VI) mRNA (10). Two other sites (HS2 and HS3) mapped at about Ϫ4.6 and Ϫ4.4 kb and were located within segments E-I and I-L, respectively (Figs.…”
Section: Chromatin Dnase I Footprinting Assayssupporting
confidence: 52%
See 2 more Smart Citations
“…6, b and c). As previously observed, one, indicated by * in the figure, was an invariant site present in all cells, whereas a second site, HS1, mapping at about Ϫ0.1 kb, was detectable in all cells expressing ␣1(VI) mRNA (10). Two other sites (HS2 and HS3) mapped at about Ϫ4.6 and Ϫ4.4 kb and were located within segments E-I and I-L, respectively (Figs.…”
Section: Chromatin Dnase I Footprinting Assayssupporting
confidence: 52%
“…Other Assays-Northern blotting, DNase I footprinting, identification of chromatin DNase I-hypersensitive sites, and electrophoretic mobility shift assays were performed exactly as described (7,10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other Assays-Northern blotting and analysis of chromatin DNase I-hypersensitive sites were performed as described previously (8,23).…”
Section: Methodsmentioning
confidence: 99%
“…The overall picture coming from these studies is a modular arrangement of regulatory regions (mostly enhancers), meaning that each region is a distinct and independent regulator of transcription in a specific tissue or in a set of tissues. Although some reports have indicated the importance of the interaction of distinct regulatory regions for high level tissue-specific transcription (7) and have shown that different basal promoters may influence expression driven by tissue-specific enhancers (8), the concept of modularity of regulatory regions is the key motif in most studies.…”
mentioning
confidence: 99%